GAMA/H-ATLAS: a meta-analysis of SFR indicators – comprehensive measures of the SFR–M* relation and cosmic star formation history at z < 0.4. Issue 1 (7th June 2016) - Davies, L. J. M.; Driver, S. P.; Robotham, A. S. G.; Grootes, M. W.; Popescu, C. C.; Tuffs, R. J.; Hopkins, A.; Alpaslan, M.; Andrews, S. K.; Bland-Hawthorn, J.; Bremer, M. N.; Brough, S.; et al.
Abstract: We present a meta-analysis of star formation rate (SFR) indicators in the Galaxy And Mass Assembly (GAMA) survey, producing 12 different SFR metrics and determining the SFR– M * relation for each. We compare and contrast published methods to extract the SFR from each indicator, using a well-defined local sample of morphologically selected spiral galaxies, which excludes sources which potentially have large recent changes to their SFR. The different methods are found to yield SFR– M * relations with inconsistent slopes and normalizations, suggesting differences between calibration methods. The recovered SFR– M * relations also have a large range in scatter which, as SFRs of the targets may be considered constant over the different time-scales, suggests differences in the accuracy by which methods correct for attenuation in individual targets. We then recalibrate all SFR indicators to provide new, robust and consistent luminosity-to-SFR calibrations, finding that the most consistent slopes and normalizations of the SFR– M * relations are obtained when recalibrated using the radiation transfer method of Popescu et al. These new calibrations can be used to directly compare SFRs across different observations, epochs and galaxy populations. We then apply our calibrations to the GAMA II equatorial data set and explore the evolution of star formation in the local Universe. We determine the evolution of the normalization to the SFR– M * relation from 0 < z < 0.35 – finding consistent trends with previous estimates at 0.3 < z < 1.2. We then provide the definitive z < 0.35 cosmic star formation history, SFR– M * relation and its evolution over the last 3 billion years.